Are Norwegian Municipality policies enabling intersectoral collaboration in migration health?. (30th September 2020) - Nordström, C; Kumar, B
Abstract: Issue: Sporadic accounts of initiatives, interventions and good practices in Migrant Health at the Municipality level account for Norways' lower score on "Measures to achieve change" in the Migrant Integration Policy Index (MIPEX). While the structure and organization at the municipality level should enable intersectoral action (as all under one umbrella), the municipal counties say lack of intersectoral collaboration is one of the main barriers for long-term public health work. Description of the Problem: 51 municipalities have an immigrant population larger than the national average 17, 8% (2019). In a recent Country Assessment (part of Joint Action on Health Equity Europe), limited inter-sectoral action on the social determinants of health including migration was observed. Although multiple agencies are engaged in attempts to address these issues. While there is a drive to promote public health and primary health care in municipalities, these initiatives do not pay special attention to migrants. In the first stage of this project, we have reviewed municipal policy documents to map policy and measures on public health, migrant health and intersectoral collaboration. In the second stage, municipalities will be contacted to engage them in the implementation of intersectoral actions. Results: The desk review and mapping show that only 8 of the "top" 32 municipalities mention "intersectoral" in the municipal master plan (5 were not available online), its mentioned in 9 action program/budgets, but not necessarily by the same municipalities. 15 of the municipalities mention migrants, but rarely in relation to health. We observe that, the size of the municipality, financial resources and support from the County are factors that may play a significant role in prioritising migrant health and intersectoral collaboration. Lessons: Advocating for and supporting the local/municipal level for intersectoral action is highly relevant, timely and essential. Key messages: Intersectoral action on the social determinants of migrants' health needs to be implemented through municipal policies to reduce inequities in migrants' health. Implementation on the local level is the main arena for good public health work and is crucial to ensure good health for migrants.